The composition of usability evaluation in assessing quality of the display case lighting / Siti Norsazlina Haron ... [et al.] - Siti Norsazlina, Haron; Norashikin, Abdul Karim; Afzanizam, Muhammad; Anuar, Talib; Md Yusof, Hamid (2015)
This paper presents and discussed discusses the need for usability evaluation as a tool to support an assessment of museum quality in-use by exploring the meaning of users‟ experiences. In this study, usability evaluation is a preliminary study to identify the design issues associated with the museum visitor‟s context of use. The finding from usability evaluation reveals that the visitors need an improvement on the lighting in the display cases. need the museum to make improvements on the lighting in the display cases. However, there are a few considerations in applying Lux reading because it will give an impact to the display artifacts. Therefore, the main case study is focusing on identifying the Lux reading in display cases for protecting the artifact and making it ideal for museum visitors. In addition, this paper provides a discussion on "usability concept and the importance of Lux reading of artifact display. Later the main study result will be validated by the museum end user to help suggest usable Lux reading. This usability evaluation is useful to the museum curator, designers and facilities management. The usability evaluation is beneficial in identifying the important usability design issues to be investigated and explored. Besides the Lux data is highly significant in improving the museum design practice and provide a guide in monitoring the performance of lighting, which is more valuable to their end-users